Platelet Count and Function during Pediatric Extracorporeal Membrane Oxygenation - Cashen, Katherine; Meert, Kathleen; Dalton, Heidi J. (Seminars in Thrombosis and Hemostasis, 2020)
Extracorporeal membrane oxygenation (ECMO) is a form of life support used to treat neonates, children, and adults with cardiorespiratory failure refractory to conventional therapy. This therapy requires the use of anticoagulation to prevent clotting in the extracorporeal circuit, but anticoagulation also increases the risk of bleeding on ECMO. Both bleeding and thrombosis remain significant complications on ECMO and balancing these risks is challenging. Acquired platelet dysfunction is common during ECMO and quantitative and qualitative platelet dysfunction contributes to bleeding risk. Optimal platelet count, function, and transfusion thresholds are not well established during pediatric ECMO. In this review, we provide an overview of hemostatic alterations during ECMO, changes in platelet count and function, platelet monitoring techniques, bleeding risk, and future needs to best optimize patient management and care.
Keywords: extracorporeal membrane oxygenation; platelets; platelet function; thrombosis; bleeding